Injectable double network hydrogel with adjustable stiffness for modulation of macrophage polarization - Jinxin Wu; Bing Han; Shili Ai; Aijing Wang; Yilin Song; Moran Jin; Xiaozhong Qu; Xiaoyan Wang (Polymer Testing)
Substrate stiffness can regulate macrophage polarization to support tissue repair in tissue engineering applications. Understanding the mechanisms of stiffness sensing is valuable for applying this knowledge to stiffness-related inflammatory diseases. In this study, we examined IACs-related integrins related to stiffness-sensitive macrophage polarization by constructing an injectable double-network (DN) hydrogel with varying stiffness. Inflammatory cytokine expression decreased as substrate stiffness increased (from 19.9 to 125.7 kPa), with medium stiffness (84.8 kPa) inducing macrophages to an increased level of anti-inflammatory polarization. Improved adhesion and elevated expression levels of ITGA5, ITGA3, and ITGAV in macrophages on the softer hydrogels highlighted the role of integrins in stiffness-regulated macrophage polarization. Inhibition of integrins using ethylenediaminetetraacetic acid (EDTA) abolished differences in macrophage polarization across the three groups, further confirming the central role of integrins. These findings suggest that, in tissue engineering, selecting appropriate substrate stiffness or gradient stiffness hydrogel could align with the optimal mechanical environment required for specific cell growth and function. Additionally, the critical role of integrins in mediating mechanical transduction may provide new therapeutic targets for treating certain stiffness-related inflammatory diseases.